2013
DOI: 10.4103/0250-474x.113544
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antimicrobial Activity of the Essential Oil from Leaves of Curcuma longa L. Kasur Variety

Abstract: The essential oil from the leaves of Curcuma longa L. Kasur variety grown in Pakistan was extracted by hydro-distillation. Chemical constituents of the essential oil were identified by gas chromatography/mass spectrometry. The chromatographic analysis of oil showed 25 constituents, out of which nine chemical constituents were identified. The eucalyptol (10.27%) was the major component of the essential oil. α-pinene (1.50%), β-phellandrene (2.49%), β-pinene (3.57%), limonene (2.73%), 1,3,8-p-menthatriene (1.76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies clearly showed that the studied EO inhibited pathogenic growth but their effectiveness varied ( Table 2). The antimicrobial activities of many EO have been reviewed and classified by previous researchers as strong, medium and weak or resistant, intermediate and sensitive (Parveen et al, 2013;Zaika, 1988). Zaika (1988) also proposed that Gram-positive bacteria are more resistant than Gram-negative bacteria to the antibacterial properties of plant volatile oils which is in contrast to the hypothesis proposed by other researchers where the susceptibility of bacteria to plant volatile oils appears to have little influence on growth inhibition (Deans and Ritchie, 1987;Deans et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The GC-MS analysis of oil showed the presence of 25 constituents and out of them eucalyptol was found to be the chief constituent. Ascaridole epoxide and some other phytoconstituents were also present in considerable amount [35]. Hydrodistillation method was used for the separation of the essential oils of the leaves of Artemisia vulgaris, Artemisia indica and Artemisia dubia and GC-MS method was used for their analysis.…”
Section: Analytical Aspect Of Ascaridolementioning
confidence: 99%